Hydroxy carboxylic acid stable type zirconium-modified niobic acid sol

JP2025030931APending Publication Date: 2025-03-07TAKI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023136649
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0006】 本発明者らは、ニオブ酸ゾルの新たな可能性を見出すべく鋭意検討した結果、触媒、電池材料、光学材料等の様々な用途において活用されているジルコニウムを用いてニオブ酸ゾルの分散粒子表面を修飾することに想到し、ジルコニウム修飾ニオブ酸ゾルを開発した。 当該ジルコニウム修飾ニオブ酸ゾルは、核粒子と該核粒子の表面を修飾する修飾物とを含む分散粒子が分散したゾルであって、該核粒子がニオブ酸を含み、該修飾物がジルコニウム成分を含み、ZrO2/Nb2O5(モル比)=0.01~0.15の範囲のものである。また、当該ジルコニウム修飾ニオブ酸ゾルは、(1)pH7以上のニオブ酸ゾルとジルコニウム化合物とを混合する第1工程、及び(2)加熱する第2工程、を含む工程によって製造することができる。 しかし、当該ジルコニウム修飾ニオブ酸ゾルは、修飾できるジルコニウム量に制約があり、上記のようにZrO2/Nb2O5のモル比では0.15以下とする必要があった。そこで、この制約にとらわれることのないジルコニウム修飾ニオブ酸ゾルについてさらに鋭意検討した結果、分散安定化剤としてヒドロキシカルボン酸を用いることが有効であることを見出し、係る知見を基に本発明を完成させた。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030931000001
    Figure 2025030931000001
Patent Text Reader

Abstract

To develop a novel niobic acid sol capable of applying to catalyst materials and battery materials.SOLUTION: A dispersed sol containing dispersed particles which include core particles and modifiers that modify the surface of the core particles, where the core particles contain niobium oxide, the modifier contains a zirconium component, and the dispersion stabilizer contains hydroxy carboxylic acid, is referred to as hydroxy carboxylic acid-stabilized zirconium-modified niobic acid sol. The hydroxy carboxylic acid-stabilized zirconium-modified niobic acid sol can be produced by a process comprising (1) a first step of mixing niobic acid sol with a pH of 7 or higher and a zirconium compound, (2) a second step of adding hydroxy carboxylic acid, and (3) a third step of heating.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a zirconium modified niobic acid sol stabilized with a hydroxycarboxylic acid. [Background technology]

[0002] Niobium oxide is used as a catalyst material taking advantage of its solid acidity. In recent years, niobium-based sol has been attracting attention as a surface coating material for positive and negative electrodes in the field of battery materials.

[0003] The applicant first invented a technology relating to ammonium niobate sol as a niobic acid sol, as described in Patent Document 1, and then invented an amine compound-stabilized niobic acid sol and an amine compound / organic acid-stabilized niobic acid sol as described in Patent Document 2, and an alkali metal-stabilized niobic acid sol as described in Patent Document 3, and further invented a lithium-phosphate-stabilized niobic acid sol as described in Patent Document 4. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5441264 [Patent Document 2] Patent No. 6156876 [Patent Document 3] Patent No. 6774158 [Patent Document 4] Patent No. 7161276 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to develop a new niobic acid sol that can be used as a catalyst material, a battery material, or the like. [Means for solving the problem]

[0006] As a result of intensive research into discovering new possibilities for niobic acid sol, the inventors came up with the idea of ​​modifying the surfaces of dispersed particles of niobic acid sol with zirconium, which is used in a variety of applications such as catalysts, battery materials, and optical materials, and developed a zirconium-modified niobic acid sol. The zirconium-modified niobic acid sol is a sol in which dispersed particles containing core particles and a modifier that modifies the surface of the core particles are dispersed, the core particles contain niobic acid, the modifier contains a zirconium component, and ZrO2 / Nb2O5 (molar ratio) is in the range of 0.01 to 0.15. The zirconium-modified niobic acid sol can be produced by a process including (1) a first step of mixing a niobic acid sol having a pH of 7 or more with a zirconium compound, and (2) a second step of heating. However, the zirconium-modified niobic acid sol is limited in the amount of zirconium that can be modified, and the molar ratio of ZrO2 / Nb2O5 must be 0.15 or less as described above. As a result of further intensive research into zirconium-modified niobic acid sol that is not bound by this restriction, it was found that using a hydroxycarboxylic acid as a dispersion stabilizer is effective, and the present invention was completed based on this finding.

[0007] The present invention is as follows. [1] A sol in which dispersed particles containing a core particle and a modifier that modifies the surface of the core particle are dispersed, the core particle containing niobic acid, the modifier containing a zirconium component, and a hydroxycarboxylic acid as a dispersion stabilizer. [2] A method for producing the hydroxycarboxylic acid stabilized zirconium-modified niobic acid sol according to the above [1], comprising the following steps: (1) A first step of mixing a niobic acid sol having a pH of 7 or more with a zirconium compound (2) The second step of adding a hydroxycarboxylic acid (3) The third step is heating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below based on preferred embodiments, but the present invention is not limited to the following embodiments and various modifications are possible within the scope of the claims. In addition, in the present invention, the expression "numeric value 1 to numerical value 2" regarding a numerical range means a numerical range including both the numerical values ​​1 and 2, with numerical value 1 being the lower limit and numerical value 2 being the upper limit, and is synonymous with "numerical value 1 or more and numerical value 2 or less."

[0009] The present invention relates to a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol (hereinafter referred to as the "sol of the present invention"), which is a sol in which dispersed particles containing a core particle and a modifying substance that modifies the surface of the core particle are dispersed, the core particle containing niobic acid, the modifying substance containing a zirconium component, and containing a hydroxycarboxylic acid as a dispersion stabilizer.

[0010] The core particles include niobic acid. A good example of the core particles is a dispersed particle in an ammonium niobate sol described in Patent Document 1, and the dispersed particle is composed of amorphous ammonium niobate. Another good example of the core particles is a dispersed particle in an amine compound stabilized niobic acid sol described in Patent Document 2, and the dispersed particle is a particle in which the ammonia content in amorphous ammonium niobate is reduced and the dispersion is stabilized by an amine compound instead of ammonia. Another good example of the core particles is a dispersed particle in an amine compound / organic acid stabilized niobic acid sol described in Patent Document 2, and the dispersed particle is a particle in which the ammonia content in amorphous ammonium niobate is reduced and the dispersion is stabilized by an amine compound and an organic acid instead of ammonia. Another good example of the core particles is a dispersed particle in an alkali metal stabilized niobic acid sol described in Patent Document 3, and the dispersed particle has the following two patterns (a) and (b). In the case of (a), it is a {complex of niobic acid and an alkali metal}, and in the case of (b), it is a {complex of niobic acid and ammonia} in addition to a {complex of niobic acid and an alkali metal}. Furthermore, the core particles may be composed of two or more types of dispersed particles among the preferred examples given above.

[0011] The modification contains a zirconium component. The modification may contain a subcomponent other than the zirconium component. Examples of the subcomponent include ammonia and alkali metals. Examples of the alkali metal include lithium, sodium, and potassium.

[0012] The dispersed particles contain the above-mentioned core particles and a modifier that modifies the surface of the core particles, and have sol properties due to the dispersed state of the dispersed particles. This dispersed state is brought about by the hydroxycarboxylic acid that is a dispersion stabilizer.

[0013] The particle size of the dispersed particles is not particularly limited as long as the properties of the sol are obtained, but for example, the average particle size of the dispersed particles is preferably within the range of 5 to 500 nm. The upper limit of the above range is more preferably 400 nm, and even more preferably 300 nm. Here, the average particle size of the dispersed particles refers to the median size when the sol of the present invention is measured using a dynamic light scattering particle size distribution analyzer "LB-500" manufactured by Horiba, Ltd.

[0014] The content of hydroxycarboxylic acid in the sol of the present invention is not particularly limited as long as it is an amount that can provide sol stabilization. For example, as such an amount, the hydroxycarboxylic acid / ZrO2 (molar ratio) is preferably in the range of 0.2 to 2.0. The lower limit of the above range is more preferably 0.3, and even more preferably 0.4. The upper limit of the above range is more preferably 1.5. Therefore, more preferable ranges of hydroxycarboxylic acid / ZrO2 (molar ratio) include 0.3 to 2.0, 0.4 to 2.0, 0.2 to 1.5, 0.3 to 1.5, and 0.4 to 1.5.

[0015] Examples of hydroxycarboxylic acids include citric acid, malic acid, lactic acid, glycolic acid, tartaric acid, etc. Only one type of hydroxycarboxylic acid may be used, or multiple types of hydroxycarboxylic acids may be used.

[0016] The ZrO2 / Nb2O5 (molar ratio) in the sol of the present invention is preferably in the range of, for example, 0.01 to 12. In this range, sol stabilization is easily obtained in the presence of hydroxycarboxylic acid. It is presumed that in the region where the molar ratio is close to 0.01, niobic acid accounts for the majority, with modifiers containing zirconium components present in part, and in the region where the molar ratio is close to 12, modifiers containing zirconium components account for the majority, with niobic acid present in part. The upper limit of the range is more preferably 11, and even more preferably 10.

[0017] The sol of the present invention has excellent stability, and can be concentrated by ultrafiltration or heating. The Nb2O5 concentration in the sol of the present invention is preferably in the range of, for example, 1 to 30 mass%. The lower limit of the concentration is more preferably 3 mass% from the economical viewpoint of production and transportation. The upper limit of 30 mass% is set from the viewpoint of avoiding deterioration of handleability due to high viscosity. Usually, the range of 6 to 20 mass%, more preferably the range of 6 to 15 mass%, is more preferable from the viewpoint of production and use. The viscosity is preferably 50 mPa·s or less. The viscosity here is measured by setting the liquid temperature of the sol of the present invention to 25°C and using an E-type viscometer "TVE-25L" (rotor: 1°34'×R24) manufactured by Toki Sangyo Co., Ltd.

[0018] A preferred method for producing the sol of the present invention comprises the following steps: (1) A first step of mixing a niobic acid sol having a pH of 7 or more with a zirconium compound (2) The second step of adding a hydroxycarboxylic acid (3) The third step is heating.

[0019] The niobic acid sol having a pH of 7 or more is not particularly limited as long as the sol has a pH of 7 or more, and examples thereof include the ammonium niobate sol described in Patent Document 1, the amine compound-stabilized niobic acid sol and the amine compound / organic acid-stabilized niobic acid sol described in Patent Document 2, and the alkali metal-stabilized niobic acid sol described in Patent Document 3. Examples of commercially available products include "Bailar Nb-G6000" manufactured by Taki Chemical Industry Co., Ltd. as an ammonium niobate sol, "Bailar Nb-G6600" manufactured by the same company as an amine compound / organic acid-stabilized niobic acid sol, and "Bailar Nb-G6700" manufactured by the same company as an alkali metal-stabilized niobic acid sol. Only one type of niobic acid sol may be used, or multiple types may be used.

[0020] The zirconium compound is preferably a zirconium salt that dissolves in water and exhibits alkalinity (water-soluble alkaline zirconium salt), and preferred examples are ammonium zirconium carbonate, potassium zirconium carbonate, etc. Only one type of zirconium compound may be used, or multiple types may be used.

[0021] A mixed liquid is obtained by mixing a niobic acid sol having a pH of 7 or more with a zirconium compound. The mixed liquid is preferably in the form of a sol. This is because if the mixed liquid gels, it becomes difficult to obtain a sol in the final product. There is no particular limitation on the mixing method, and mixing may be performed by a conventional method. For example, a zirconium compound is added to a niobic acid sol under stirring. The zirconium compound may be liquid or solid, but it is particularly preferable to use a liquid. In addition, when a solid is used, it is particularly preferable to use a powder, and it may be dispersed in a small amount of water. There is no particular limitation on the method of preparing the mixed liquid, but preferably, the niobic acid sol is made into an aqueous solution of Nb2O5=0.1 to 5.0 mass%, and this is mixed with a zirconium compound to obtain a mixed liquid having sol-like properties. In this case, if a liquid zirconium compound is used, it is preferable that the ZrO2 concentration is in the range of 0.1 to 5.0 mass%.

[0022] In the second step, a hydroxycarboxylic acid is added to the mixed liquid obtained in the first step. Preferably, a solid (preferably granular, powdery, etc.) hydroxycarboxylic acid is added to the mixed liquid under stirring.

[0023] In the third step, the mixture obtained in the second step is heated. The heating is not particularly limited as long as a sol is obtained, and for example, the heating temperature is preferably in the range of 100 to 200°C. The lower limit of the above range is more preferably 110°C, and the upper limit is more preferably 150°C. Thus, more preferred heating temperature ranges include 100 to 150°C, 110 to 200°C, and 110 to 150°C. The heating time may be appropriately adjusted depending on the heating temperature, and is preferably in the range of, for example, 1 to 8 hours.

[0024] After the third step, any step may be carried out, such as a washing step, a concentration adjustment step, etc. There is no particular limitation on the washing method, but ultrafiltration while adding water is preferred.

[0025] Although the mechanism by which the surface of the core particles is modified by the modifier is not clear, it is assumed that the modifier is present in a state of being bound or adsorbed to the surface of the core particles. In terms of the zirconium component, it is assumed that the zirconium component derived from the zirconium compound neutralized or hydrolyzed by the niobic acid on the surface of the core particles by heating in the third step is bound or adsorbed. The form of the zirconium component as a compound is thought to be zirconium oxide or zirconium hydroxide.

[0026] The sol of the present invention can be suitably used for various applications, such as additives for catalysts, secondary batteries, electronic materials, and coating additives. EXAMPLES

[0027] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0028] (raw materials) The ammonium niobate sol used was "Baylal Nb-G6000" (Nb2O5 concentration: 6 mass%, pH 8) manufactured by Taki Chemical Co., Ltd. The amine compound / organic acid stabilized niobate sol used was "Baylal Nb-G6600" (Nb2O5 concentration: 6 mass%, pH 8) manufactured by the same company, and the alkali metal stabilized niobate sol used was "Baylal Nb-G6700" (Nb2O5 concentration: 6 mass%, pH 8) manufactured by the same company.

[0029] Example 1 189g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 944g of ion-exchanged water. 2.9g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) was added to 55g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed with this solution. Next, 0.5g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 0.5) was added under stirring, and then heated at 130°C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 1 with a ZrO2 / Nb2O5 (molar ratio) of 0.11.

[0030] Example 2 163 g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 815 g of ion-exchanged water. A solution prepared by adding 185 g of ion-exchanged water to 9.7 g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) to prepare 1.0 mass% as ZrO2 was added and mixed to this liquid. Next, 3.3 g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 130 ° C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 2 with a ZrO2 / Nb2O5 (molar ratio) of 0.42.

[0031] Example 3 163 g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 815 g of ion-exchanged water. 9.7 g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) was added to 185 g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed with this solution. Next, 3.3 g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 140 ° C for 3 hours. Then, the mixture was concentrated using an ultrafiltration device to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 3 with a ZrO2 / Nb2O5 (molar ratio) of 0.42.

[0032] Example 4 131 g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 654 g of ion-exchanged water. 18.2 g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) was added to 346 g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed with this solution. Next, 2.5 g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 0.4) was added under stirring, and then heated at 110 ° C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 4 with a ZrO2 / Nb2O5 (molar ratio) of 1.0.

[0033] Example 5 131 g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 654 g of ion-exchanged water. 18.2 g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) was added to 346 g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed with this solution. Next, 6.2 g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 130 ° C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 5 with a ZrO2 / Nb2O5 (molar ratio) of 1.0.

[0034] Example 6 131g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 654g of ion-exchanged water. 18.2g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) was added to 346g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed with this solution. Next, 6.2g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 140°C for 3 hours. Then, the mixture was concentrated using an ultrafiltration device to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 6 with a ZrO2 / Nb2O5 (molar ratio) of 1.0.

[0035] Example 7 448g of ion-exchanged water was added to 90g of ammonium niobate sol to dilute it to 1.0% by mass as Nb2O5. A solution prepared by adding 552g of ion-exchanged water to 29g of ammonium zirconium carbonate (ZrO2 concentration: 20% by mass) to prepare 1.0% by mass as ZrO2 was added and mixed to this liquid. Next, 5.0g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 0.5) was added under stirring, and then heated at 130°C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 7 with a ZrO2 / Nb2O5 (molar ratio) of 2.3.

[0036] Example 8 173g of ion-exchanged water was added to 35g of ammonium niobate sol to dilute it to 1.0 mass% as Nb2O5. A solution prepared by adding 824g of ion-exchanged water to 43g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) to prepare 1.0 mass% as ZrO2 was added and mixed to this liquid. Next, 7.4g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 0.5) was added under stirring, and then heated at 130°C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 8 with a ZrO2 / Nb2O5 (molar ratio) of 9.0.

[0037] Example 9 131 g of ammonium niobate sol was diluted to 1.0 mass% as Nb2O5 by adding 655 g of ion-exchanged water. 19.2 g of potassium zirconium carbonate (ZrO2 concentration: 19 mass%) was added to 345 g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed with this solution. Next, 6.2 g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 140 ° C for 3 hours. Then, the mixture was concentrated using an ultrafiltration device to obtain a hydroxycarboxylic acid-stabilized zirconium-modified niobic acid sol of Example 9 with a ZrO2 / Nb2O5 (molar ratio) of 1.0.

[0038] Example 10 131 g of amine compound / organic acid stabilized niobic acid sol was diluted to 1.0 mass% as Nb2O5 by adding 654 g of ion-exchanged water. 18.2 g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) was added to 346 g of ion-exchanged water to prepare a solution of 1.0 mass% as ZrO2, and mixed. Next, 6.2 g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 140 °C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid stabilized zirconium modified niobic acid sol of Example 10 with a ZrO2 / Nb2O5 (molar ratio) of 1.0.

[0039] Example 11 654g of ion-exchanged water was added to 131g of alkali metal stabilized niobic acid sol to dilute it to 1.0 mass% as Nb2O5. A solution prepared by adding 346g of ion-exchanged water to 18.2g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) to prepare 1.0 mass% as ZrO2 was added and mixed to this liquid. Next, 6.2g of citric acid monohydrate (molar ratio of citric acid / ZrO2 = 1.0) was added under stirring, and then heated at 140°C for 3 hours. Then, the mixture was concentrated using an evaporator to obtain a hydroxycarboxylic acid stabilized zirconium modified niobic acid sol of Example 11 having a ZrO2 / Nb2O5 (molar ratio) of 1.0.

[0040] Comparative Example 1 In Example 8, citric acid was not added. That is, 173 g of ion-exchanged water was added to 35 g of ammonium niobate sol to dilute it to 1.0 mass% as Nb2O5. A solution prepared by adding 824 g of ion-exchanged water to 43 g of ammonium zirconium carbonate (ZrO2 concentration: 20 mass%) to prepare 1.0 mass% as ZrO2 was added and mixed (molar ratio of ZrO2 / Nb2O5 = 9.0). This was heated at 130°C for 3 hours, but the liquid became cloudy, the generation of precipitate was observed, and no sol was obtained.

[0041] [Reference example 1] To 1000 g of ammonium niobate sol under stirring, 15.4 g of an aqueous solution of ammonium zirconium carbonate (ZrO2 concentration: 20% by mass) was added, and then heated at 100°C for 2 hours to obtain a zirconium-modified niobate sol of Reference Example 1 having a ZrO2 / Nb2O5 (molar ratio) of 0.11 and an Nb2O5 concentration of 5.9% by mass.

[0042] [Reference example 2] To 1,000 g of ammonium niobate sol under stirring, 7.7 g of an aqueous solution of potassium zirconium carbonate (ZrO2 concentration: 19 mass%) was added, and then heated at 100°C for 2 hours to obtain a zirconium-modified niobate sol of Reference Example 2 having a ZrO2 / Nb2O5 (molar ratio) of 0.05 and an Nb2O5 concentration of 5.8 mass%.

[0043] [Reference example 3] To 1,000 g of ammonium niobate sol under stirring, 21.9 g of an aqueous solution of potassium zirconium carbonate (ZrO2 concentration: 19% by mass) was added, and the mixture was heated at 100°C for 2 hours. Ion-exchanged water was then added to obtain a zirconium-modified niobic acid sol of Reference Example 3 having a ZrO2 / Nb2O5 (molar ratio) of 0.15 and an Nb2O5 concentration of 3.1% by mass.

[0044] (Analysis method) The hydroxycarboxylic acid stabilized zirconium modified niobic acid sols obtained in Examples 1 to 11 were subjected to the following analyses as they were. pH: Measured using a Horiba pH meter "D-53." ·EC: Measured using an EC meter "CM42-X" manufactured by DKK-TOA Corporation. Haze and total light transmittance: Measured using a haze meter "COH7700" manufactured by Nippon Denshoku Industries Co., Ltd., at wavelengths of 400 to 700 nm (10 nm intervals) and an optical path length of 10 mm. Average particle size: Measured using a dynamic light scattering particle size distribution analyzer "LB-500" manufactured by Horiba Ltd. Viscosity: The liquid temperature was set to 25°C and measurements were taken using a Toki Sangyo Co., Ltd. E-type viscometer "TVE-25L" (rotor: 1°34' x R24).

[0045] The results are shown in Table 1.

[0046] [Table 1]

Claims

1. A sol in which dispersed particles containing core particles and a modifying substance that modifies the surface of the core particles are dispersed, the core particles contain niobic acid; the modification comprises a zirconium component; Contains hydroxycarboxylic acid as a dispersion stabilizer, Hydroxycarboxylic acid stabilized zirconium modified niobic acid sol.

2. 2. A method for producing the hydroxycarboxylic acid stabilized zirconium modified niobic acid sol of claim 1, comprising the steps of: (1) A first step of mixing a niobic acid sol having a pH of 7 or more with a zirconium compound (2) The second step of adding a hydroxycarboxylic acid (3) The third step is heating.

Citation Information

Patent Citations

  • Method of bending noncircular aluminum pipe

    JP1979041264A

  • Safety mechanism of power supply switch for battery type electric tool

    JP1986056876A

  • Alkali metal stabilized niobate sol

    JP6774158B2

  • Lithium-phosphate stabilized niobate sol

    JP7161276B2